Analisis Deskriptif Lo Cooler Gearbox Pada Mesin Induk di Km. Binaiya - Valentino, Yunan; Darul prayogo; Retno haryanti (Politeknik Ilmu Pelayaran Semarang, 2025)
Maritime transportation plays a vital role in supporting Indonesia’s economy as an archipelagic nation. One of the crucial aspects of maintaining ship operations is the lubrication system of the main engine gearbox, which uses a Lo Cooler as an auxiliary device to cool the lubricating oil. This research employs a descriptive qualitative method through direct observation, interviews with the First Engineer and Chief Engineer (KKM), and documentation during sea practice on KM. Binaiya. The findings show that the main causes of leakage include cracked Lo Cooler tubes due to corrosion and sediment buildup, unstable lubricating oil pressure, elevated oil temperatures, and improper gasket installation. The handling efforts include regular maintenance, maintaining proper oil pressure and temperature, and repairing damaged tubes and gaskets. This research highlights the importance of routine inspections and lubrication system maintenance to prevent serious disruptions in ship operations.